Dielectric, elastic and optical properties of 80TeO2-(20-x)MnO2-xFe2O3 and 30Li2O-4MoO3-(66-x)TeO2-xV2O5 mixed oxide tellurite glasses in the conductivity anomaly region / Rosdiyana Hasham@Hisam - Hasham@Hisam, Rosdiyana (2017)
In this study, two series of mixed oxide tellurite based glasses with composition 80TeO2-(20-x)MnO2-xFe2O3 (x = 5 mol% to 20 mol%) and 30Li2O-4MoO3-(66x) TeO2-xV2O5 (x = 0.2-1.2 mol%) were prepared using melt-quenching method to investigate their dielectric, AC conductivity, elastic and optical properties. For the 80TeO2-(20-x)MnO2-xFe2O3 glass samples, the dielectric constant showed strong variation with Fe2O3 at a frequency ≥10 kHz, where έ decreased to a minimum value at x = 10 mol% before increasing for x>10%. The decrease in έ may be attributed to some form of hindrance effect on heavy dipoles caused by the mixed transition-ion effect (MTE). Meanwhile, variation of AC conductivity with Fe2O3 showed non-linear increase for x ≤10 mol% before dropping to a minimum at 15 mol% Fe2O3. This result is attributed to Anderson localization because of the disorder in the glass system. On the other hand, DC conductivity for the same glass system showed a strong increase for x ≤10 mol% Fe2O3 before reaching a saddle-like behavior between 10 mol % ≤x ≤15 mol%, followed by a large increase for x> 15 mol%. Independent longitudinal modulus (CL), shear modulus (µ) and bulk modulus (Ke) showed increased values for x ≤10 mol% with an anomalous drop at x = 15 mol% Fe2O3, followed by a large increase at x > 15 mol%. The anomalous region between 10 mol% ≤x≤15 mol% coincided with DC conductivity saddle-like region and is suggested to be related to the MTE. Meanwhile, in the same region, optical band gap (Eopt) exhibited a maxima, whereas refractive index showed a minima, thereby indicating a variation in polarizability due to changes in concentration of bridging and non-bridging oxygens. For the 30Li2O-4MoO3-(66-x)TeO2-xV2O5 glasses, the variation of AC conductivity with V2O5 showed a non-linear increase for x ≤0.6 mol% before decreasing to a minimum at 0.8 mol% V2O5. The decrease in σAC is attributed to some forms of blocking effect on Li+ ions caused by the mixed ionic-electronic (MIE) effect. Meanwhile, dielectric constant showed a general increase for x ≤ 0.6 before an anomalous decrease at x = 0.8 mol% V2O5, which was followed by a large increase at x> 0.8 mol%. The decrease at x = 0.8 mol% coincided with the σAC drop at the same location. This decrease was also suggested to be related to the MIE that induced a blocking effect, which caused the restricted dipole movement. Meanwhile, DC conductivity showed initial weak increase for x ≤0.6 mol% V2O5 before decreasing sharply at x = 0.8 mol% followed by a large increase for x> 0.8 mol%. Independent longitudinal modulus (CL), shear modulus (µ) and related elastic modulus also exhibited non-linear behavior where their values decreased to a minimum at x = 0.8 mol% before increasing beyond x = 0.8 mol% with the addition of V2O5. The decrease in elastic modulus for x ≤0.8 mol% indicated a decrease in stiffness and rigidity of the glasses due to increase in non-bridging oxygen (NBO) contributed by TeO3 and MoO3 which weakened the glass network. Subsequently, a large increase at x> 0.8 mol% is suggested to be due the increase in BO contributed by VO5 together with the formation of strong covalent V-O bond. The anomalous region at x = 0.8 mol% which coincided with the DC conductivity minimum region is suggested to be related to the (MIE) effect. Meanwhile, in the same region, optical band gap (Eopt) and refractive index (n) exhibited an off-trend behavior indicating variation in polarizability due to changes in concentration of bridging and non-bridging oxygen.